2021
DOI: 10.1039/d0cc08096a
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-promoted ring-opening methylation of benzothiazoles with dimethyl sulfite

Abstract: A new methylation of N,S-atoms using dimethyl sulfite as a safe and cheap methylating reagent through halogen bond promoted ring-opening coupling of benzothiazoles is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Then, T o , which refers to the temperature when ΔG°is zero, is calculated (T o = ΔH o /ΔS o ) according to the above hypothesis. From Table 1, it can be concluded that T o ranges from 38.76 to 80.02 °C when ΔG°R D (XH •+ ) increased 15 K are considered to be potential methyl radical reagents in organic synthesis (Figure 1). 33 Nine XH •+ s (5H •+ , 6H •+ , 9H •+ , 10H •+ , 12H •+ , 13H •+ , 15H •+ , 43H •+ , and 45H •+ , Scheme 3) in this work are found to be potential methyl radical reagents in organic synthesis, with ΔG°R D (XH •+ ) ranging from 2.67 (15H •+ ) to 4.81 kcal/mol (45H •+ ) and ΔG RD ≠ (XH •+ ) ranging from 15.84 (5H •+ ) to 18.91 kcal/mol (13H •+ ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, T o , which refers to the temperature when ΔG°is zero, is calculated (T o = ΔH o /ΔS o ) according to the above hypothesis. From Table 1, it can be concluded that T o ranges from 38.76 to 80.02 °C when ΔG°R D (XH •+ ) increased 15 K are considered to be potential methyl radical reagents in organic synthesis (Figure 1). 33 Nine XH •+ s (5H •+ , 6H •+ , 9H •+ , 10H •+ , 12H •+ , 13H •+ , 15H •+ , 43H •+ , and 45H •+ , Scheme 3) in this work are found to be potential methyl radical reagents in organic synthesis, with ΔG°R D (XH •+ ) ranging from 2.67 (15H •+ ) to 4.81 kcal/mol (45H •+ ) and ΔG RD ≠ (XH •+ ) ranging from 15.84 (5H •+ ) to 18.91 kcal/mol (13H •+ ).…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of the methyl group to drug molecules is helpful to improve their binding affinity, biological availability, and metabolic stability (called “magic methyl effect”), which greatly changes the pharmacological properties of bioactive molecules. Methylation plays an important role in the modification of drug molecules, DNA, as well as proteins. According to different reaction mechanisms, the methylation agents are divided into three classes, i.e., electrophilic methylation reagents, nucleophilic methylation reagents, and free radical methylation reagents . At present, great progress has been made in the methylation reaction. Many chemists have made outstanding contributions in this field, and a large number of new methyl reagents and new methylation reactions have been developed, especially electrocatalytic, , visible-light-induced, or transition-metal-catalyzed methylation, in recent years. In 2021, Dixon and co-workers published an important review about C–H methylation in chemical synthesis, which covered the various methylation reagents and diverse strategies employed to realize the selective installation of the C–Me bond in extensive chemical structures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, sulfites have been found as versatile SO 2 donors in some sulfonylations . We also developed a methylation reaction using dimethyl sulfite as methylating reagent . Encouraged by these results, we envision whether dimethyl sulfite could be applied as both sulfur dioxide donor and methyl source in some methylsulfonylations.…”
mentioning
confidence: 96%
“…13 We also developed a methylation reaction using dimethyl sulfite as methylating reagent. 14 Encouraged by these results, we envision whether dimethyl sulfite could be applied as both sulfur dioxide donor and methyl source in some methylsulfonylations. Herein, we report a Pd-catalyzed methylsulfonylation of aryl/alkyl iodides with dimethyl sulfite to directly produce methyl sulfone derivatives under ligand-and base-free reaction conditions (Scheme 2, eq c).…”
mentioning
confidence: 99%